What “blindness” to gender differences helps women see and do: Implications for confidence, agency, and action in male-dominated environments - Martin, Ashley E.; Phillips, Katherine W. (Organizational behavior and human decision processes, 2017)
•Beliefs about how to approach differences have effects on women’s confidence and action-taking.•Downplaying gender differences (gender-blindness) increased women’s confidence and action-taking.•This strategy neutralized the confidence gap between men and women .•Effects occurred through women’s identification with agency and were stronger in male-dominated contexts. The ways in which we discuss gender (embracing vs. downplaying difference) has implications for women’s workplace confidence and behavior, especially in male-dominated environments and positions of power. In five total studies (N=1453), across a variety of samples, we found that gender-blindness—the belief that gender differences should be downplayed—is a more adaptive strategy for increasing female workplace confidence than gender-awareness—the belief that gender differences should be celebrated. In addition to increasing confidence, gender-blindness was related to actions necessary for reducing gender disparities (e.g., risk-taking, negotiation). We found that perceived gender differences in agency (i.e., assertiveness, independence) accounts for gender differences in workplace confidence, especially in male-dominated environments (e.g., business school) and positions of power (managerial positions). Finally, we found that gender-blindness either lessened or had no effect on men’s confidence, demonstrating the unique positive effect of gender-blindness on women’s confidence. Together, this research highlights the potential for downplaying differences, instead of emphasizing them, to combat the confidence gap.